Predicting marital conflicts based on women's attachment styles on the verge of divorce: The mediating role of early maladaptive schemas - Adlparvar, Effat; Safaeirad, Iraj; Erfani, Nasrollah; Jadidi, Hooshang (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to develop a causal model of marital conflict based on attachment styles with the mediating role of early maladaptive schemas in women on the verge of divorce. Research Method: This research is a multivariate correlation study in terms of applied purpose and descriptive data collection. However, in order to finally present the results in a model, structural equations have been used. The statistical population of this study includes all women with marital conflicts on the verge of divorce in Tehran who in 1391 referred to family counseling centers in the third district of Tehran. The sampling method used in this study is available (targeted) cluster sampling, which is randomly selected from different urban areas of an area, then selected from counseling centers in that area. Data: Marital Conflict Questionnaire, Barati and Sanaei, Hazen and Shaver Attachment Styles Questionnaire and Young Young Early Incompatible Schemas were used. Results: The results showed that there is a positive and significant relationship between early maladaptive schemas in the field of cut and exclusion, self-regulation and impaired function, impaired constraints, excessive ringing and inhibition with marital conflicts; The results also showed that there is a positive and significant relationship between avoidant / ambivalent insecure attachment styles and early maladaptive schemas in the field of cut and rejection, impaired autonomy and function, impaired constraints, excessive ringing and inhibition; But there is a negative relationship between secure attachment style and early maladaptive schemas. Conclusion: The results show that the design of a suitable structural model for predicting marital conflicts based on attachment styles and the mediating role of early maladaptive schemas in women on the verge of divorce is consistent with the theoretical model and has a good fit.